Using the Earth as a Polarized Electron Source to Search for Long-Range Spin-Spin Interactions - Hunter, Larry; Gordon, Joel; Peck, Stephen; Ang, Daniel; Lin, Jung-Fu (Science (American Association for the Advancement of Science), 2013)
Many particle-physics models that extend the standard model predict the existence of long-range spin-spin interactions. We propose an approach that uses the Earth as a polarized spin source to investigate these interactions. Using recent deep-Earth geophysics and geochemistry results, we create a comprehensive map of electron polarization within the Earth induced by the geomagnetic field. We examine possible long-range interactions between these spin-polarized geoelectrons and the spin-polarized electrons and nucleons in three laboratory experiments. By combining our model and the results from these experiments, we establish bounds on torsion gravity and possible long-range spin-spin forces associated with the virtual exchange of either spin-one axial bosons or unparticles.